Characteristics of the mental situation involved in the addictive consumption of drugs and the motivation to enter an addiction treatment - López Acosta, Cristián (Revista de Psicología, 2011)
This article contains the results of a research regarding the characteristics of the mental situation of individuals that have developed an addiction, during the stage previous to seek advice. This psychic situation is related to the difficulty of the decision process involved in entering a treatment, typical in these patients. As from the results, a discussion arises entailing the concept of motivation in relation to a treatment and the technical elements that are associated thereof. It is discussed also, the relevance of including significant others, and the importance of achieving an initial suspension of the drugs consumption.